Nostalgia-Based Co-Branding Strategy Influencing Consumer Decisions in Kinder Joy Products - Anjali Janapalli; Batchu Varshini; Gurram Manasa (Involvement International Journal of Business, 2026)
Nostalgia has become an increasingly relevant marketing strategy for influencing consumer decisions through emotional memory and symbolic brand associations. However, limited empirical evidence explains how nostalgia-based co-branding strategies affect purchase intention, especially in confectionery products. This study investigates the influence of nostalgia-based collaboration on consumer decisions toward Kinder Joy products, focusing on emotional motivation, purchase intention, and the role of social media awareness. This study employed a quantitative explanatory design using primary data collected through an online questionnaire. A total of 234 respondents participated in the survey. Data were analyzed using descriptive statistics, cross-tabulation, regression analysis, and chi-square testing to examine the relationship between nostalgia appeal, co-branding collaboration, consumer awareness, and purchase behavior. The results show that 41.1% of respondents expressed likely or very likely purchase intention toward nostalgia-based collaboration products. Emotional nostalgia related to Kinder Joy childhood memories (32.5%) and attachment to the Harry Potter franchise (29.9%) were stronger purchase drivers than advertising (23.1%). Social media was identified as the dominant awareness channel, with 54.5% of respondents first discovering the product through digital platforms. Regression analysis confirmed a statistically significant positive effect of nostalgia-based collaboration on purchase intention (p < 0.001). The study concludes that nostalgia-based co-branding is an effective strategy for increasing consumer interest by combining emotional memory, franchise popularity, and digital amplification. Firms are encouraged to integrate nostalgic storytelling with strategic partnerships and social media engagement to strengthen market performance. Future research should explore broader markets, comparative product categories, and mediating psychological variables.